let D be non empty set ; :: thesis: for i being natural Number

for T1, T2 being Tuple of i,D

for F being BinOp of D

for u being UnOp of D holds (F * ((id D),u)) .: (T1,T2) = F .: (T1,(u * T2))

let i be natural Number ; :: thesis: for T1, T2 being Tuple of i,D

for F being BinOp of D

for u being UnOp of D holds (F * ((id D),u)) .: (T1,T2) = F .: (T1,(u * T2))

let T1, T2 be Tuple of i,D; :: thesis: for F being BinOp of D

for u being UnOp of D holds (F * ((id D),u)) .: (T1,T2) = F .: (T1,(u * T2))

let F be BinOp of D; :: thesis: for u being UnOp of D holds (F * ((id D),u)) .: (T1,T2) = F .: (T1,(u * T2))

let u be UnOp of D; :: thesis: (F * ((id D),u)) .: (T1,T2) = F .: (T1,(u * T2))

for T1, T2 being Tuple of i,D

for F being BinOp of D

for u being UnOp of D holds (F * ((id D),u)) .: (T1,T2) = F .: (T1,(u * T2))

let i be natural Number ; :: thesis: for T1, T2 being Tuple of i,D

for F being BinOp of D

for u being UnOp of D holds (F * ((id D),u)) .: (T1,T2) = F .: (T1,(u * T2))

let T1, T2 be Tuple of i,D; :: thesis: for F being BinOp of D

for u being UnOp of D holds (F * ((id D),u)) .: (T1,T2) = F .: (T1,(u * T2))

let F be BinOp of D; :: thesis: for u being UnOp of D holds (F * ((id D),u)) .: (T1,T2) = F .: (T1,(u * T2))

let u be UnOp of D; :: thesis: (F * ((id D),u)) .: (T1,T2) = F .: (T1,(u * T2))

now :: thesis: (F * ((id D),u)) .: (T1,T2) = F .: (T1,(u * T2))

hence
(F * ((id D),u)) .: (T1,T2) = F .: (T1,(u * T2))
; :: thesis: verumend;